2014
DOI: 10.1080/17513758.2014.904526
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle dynamics in a response/signalling feedback system with a gap

Abstract: We consider a dynamical model of cell cycles of n cells in a culture in which cells in one specific phase (S for signalling) of the cell cycle produce chemical agents that influence the growth/cell cycle progression of cells in another phase (R for responsive). In the case that the feedback is negative, it is known that subpopulations of cells tend to become clustered in the cell cycle; while for a positive feedback, all the cells tend to become synchronized. In this paper, we suppose that there is a gap betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…55,56 Cluster growth is beneficial to cell proliferation and function recovery. 57 The observations indicated that doping of Sr enhanced the bioactivity of the rMBG.…”
Section: Influence Of Bioglass Nanoparticles On In Vitro Cell Viabilitymentioning
confidence: 97%
“…55,56 Cluster growth is beneficial to cell proliferation and function recovery. 57 The observations indicated that doping of Sr enhanced the bioactivity of the rMBG.…”
Section: Influence Of Bioglass Nanoparticles On In Vitro Cell Viabilitymentioning
confidence: 97%